Bacteriological etiology and treatment of mastitis in Finnish dairy herds - Johanna Vakkamäki (Acta Veterinaria Scandinavica, 2017)
Abstract Background The Finnish dairy herd recording system maintains production and health records of cows and herds. Veterinarians and farmers register veterinary treatments in the system. Milk samples for microbiological analysis are routinely taken from mastitic cows. The laboratory of the largest dairy company in Finland, Valio Ltd., analyzes most samples using real-time PCR. This study addressed pathogen-specific microbiological data and treatment and culling records, in combination with cow and herd characteristics, from the Finnish dairy herd recording system during 2010–2012. Results The data derived from 240,067 quarter milk samples from 93,529 dairy cows with mastitis; 238,235 cows from the same herds served as the control group. No target pathogen DNA was detected in 12% of the samples. In 49% of the positive samples, only one target species and in 19%, two species with one dominant species were present. The most common species in the samples with a single species only were coagulase-negative staphylococci (CNS) (43%), followed by Staphylococcus aureus (21%), Streptococcus uberis (9%), Streptococcus dysgalactiae (8%), Corynebacterium bovis (7%), and Escherichia coli (5%). On average, 36% of the study cows and 6% of the control cows had recorded mastitis treatments during lactation. The corresponding proportions were 16 and 6% at drying-off. For more than 75% of the treatments during lactation, diagnosis was acute clinical mastitis. In the milk samples from cows with a recorded mastitis treatment during lactation, CNS and S. aureus were most common, followed by streptococci. Altogether, 48% of the cows were culled during the study. Mastitis was reported as the most common reason to cull; 49% of study cows and 18% of control cows were culled because of mastitis. Culling was most likely if S. aureus was detected in the milk sample submitted during the culling year. Conclusions The PCR test has proven to be an applicable method also for large-scale use in bacterial diagnostics. In the present study, microbiological diagnosis was unequivocal in the great majority of samples where a single species or two species with one dominating were detected. Coagulase-negative staphylococci and S. aureus were the most common species. S. aureus was also the most common pathogen among the culled cows, which emphasizes the importance of preventive measures.